EORTC QLQ-C30 Descriptive Analysis with the qlqc30 Command. (December 2015) - Bascoul-Mollevi, Caroline; Castan, Florence; Azria, David; Gourgou-Bourgade, Sophie
Health-related quality of life is often an endpoint in oncology clinical trials. The European Organization for Research and Treatment of Cancer (EORTC) developed the cancer-specific quality of life questionnaire (QLQ-C30), which includes five functions, nine symptoms, and a global health status. These questionnaires are completed by the patients themselves throughout the process of care. The recommended approaches for processing EORTC QLQ-C30 data are usually descriptive and graphic. Our aim was to develop a user-written command that provided an automatic descriptive analysis of EORTC QLQ-C30 data, consisting of profile plots per visit and longitudinal plots per functional and symptom scale.